The assessment of malnutrition and severity of gastrointestinal disease by using symptom-based questionnaires in systemic sclerosis: is it related to severe organ involvement or capillary rarefaction at microcirculation? - (:unkn) unknown (My University, 2020)
OBJECTIVES: Gastrointestinal (GI) system is commonly affected in sytemic sclerosis (SSc) patients who are also known to be at risk for malnutrition. We aimed to investigate the relationship between severity of GI disease, malnutrition and severity of organ involvement including microvasculopathy. METHODS: A hundred and thirty-four SSc patients were included into the study; disease activity and severity, the University of California, Los Angeles, Scleroderma Clinical Trials Consortium Scleroderma Gastrointestinal scale 2.0 (UCLA SCTC GIT 2.0) and malnutrition universal screening tool (MUST) were cross-sectionally assessed. Nailfold video-capillaroscopy(NVC) was performed to evaluate microvasculopathy. RESULTS: SSc patients who are at medium to high risk for malnutrition (n=20); had more frequently limited pulmonary function, lung involvement, pulmonary hypertension, capillary rarefaction and NVC late pattern than those at low risk for malnutrition. Capillary rarefaction (≤6/mm) was shown to be independently associated with medium to high risk for malnutrition defined by using MUST. Capillary rarefaction and severe skin involvement were found to be independently related to 'severe' or 'very severe' GI disease defined by using UCLA SCTC GIT 2.0. UCLA SCTC GIT 2.0 scores were not found to be good discriminative in patients at risk for malnutrition allowing for a ROC curve of area under the curve (AUC)<0.8). CONCLUSIONS: Assessment of gastrointestinal complaints and nutritional status by using symptom based questionnaires reflected the severity of GI disease and malnutrition including some limitations. Capillary rarefaction and severe skin involvement might be determining factors for malnutrition risk and severe GI disease.
Keywords: Humans; Surveys and Questionnaires; Severity of Illness Index; Gastrointestinal Diseases; Scleroderma, Systemic; Malnutrition; Microcirculation; Microvascular Rarefaction